Associations between common polymorphisms in TP53 and p21WAF1/Cip1 and phenotypic features of breast cancer - Powell, Brenda L.; van Staveren, Iris L.; Roosken, Paul; Grieu, Fabienne; Berns, Els M.J.J.; Iacopetta, Barry (Carcinogenesis (New York), 2002)
The tumour suppressor gene TP53 and its downstream effector p21 are thought to play major roles in the development of breast cancer. We investigated three common sequence variants in TP53 and p21 for possible associations with the risk of breast cancer and with various phenotypic features of this disease. A total of 351 cases were available for study. Germline DNA obtained from female subjects of similar age but without cancer was used to estimate the TP53 and p21 genotype frequencies in a control population. A single nucleotide polymorphism in intron 2 of p21 was associated with slightly increased breast cancer risk (RR = 1.4, P = 0.011) and with well/moderately differentiated tumour histology (P = 0.029). The 16 bp insertion polymorphism in intron 3 of TP53 was associated with poor histological grade (OR = 2.3, P = 0.013) independently of other pathological features. The codon 31 polymorphism in p21 was strongly linked to negative progesterone receptor status (OR = 3.4, P = 0.0001), suggesting this variant may have functional significance for the progesterone signalling pathway in breast cancer. These results add to the growing body of evidence that genetic variants can influence not only the risk of breast cancer but also the disease phenotype.